Toe pressure and toe brachial index are predictive of cardiovascular mortality regardless of the most diseased arterial segment in symptomatic lower-extremity artery disease—A retrospective cohort study - Koivunen Veerakaisa; Juonala Markus; Venermo Maarit; Laivuori Mirjami; Jalkanen Juho M.; Hakovirta Harri (Public Library of Science, 2022)
Objective
Although lower extremity arterial disease (LEAD) is most often multisegmental, the predominant disease location and risk factors differ between patients. Ankle-brachial index (ABI), toe-brachial index (TBI), and toe pressure (TP) are predictive of outcome in LEAD patients. Previously, we reported a classification method defining the most diseased arterial segment (MDAS); crural (CR), femoropopliteal (FP), or aortoiliac (AOI). Current study aimed to analyze the associations between MDAS, peripheral pressure measurements and cardiovascular mortality.
Materials and methods
We reviewed retrospectively 729 consecutive LEAD patients (Rutherford 2–6) who underwent digital subtraction angiography between January, 2009 to August, 2011 and had standardized peripheral pressure measurements.
Results
In Cox Regression analyses, cardiovascular mortality was associated with MDAS and non-invasive pressure indices as follows; MDAS AOI, TP <30 mmHg (HR 3.00, 95% CI 1.13–7.99); MDAS FP, TP <30 mmHg (HR 2.31, 95% CI 1.36–3.94), TBI <0.25 (HR 3.20, 95% CI 1.34–7.63), ABI <0.25 (HR 5.45, 95% CI 1.56–19.0) and ≥1.30 (HR 6.71, 95% CI 1.89–23.8), and MDAS CR, TP <30 mmHg (HR 4.26, 95% CI 2.19–8.27), TBI <0.25 (HR 7.71, 95% CI 1.86–32.9), and ABI <0.25 (HR 2.59, 95% CI 1.15–5.85).
Conclusions
Symptomatic LEAD appears to be multisegmental with severe infrapopliteal involvement. Because of this, TP and TBI are strongly predictive of cardiovascular mortality and they should be routinely measured despite the predominant disease location or clinical presentation.